Knowledge of General Practitioner’s toward Spondyloarthritis (SpA): A Qualitative Study - Mirza Zaka Pratama; Cesarius Wahono; Nabila Mukti; Perdana Rahman (Universitas Brawijaya, 2022)
Background: Low back pain (LBP) is one of major health problems experienced by 80-85% of patients in their lifetime. Spondyloarthritis (SpA) has become one of the leading causes of chronic LBP but is often undiagnosed. General practitioners (GP) have an essential role in the early diagnosis of SpA. Aim: To explore the knowledge of GP about SpA from clinical diagnosis and early management and elaborate on each GP’s clinical perspective and practice performance. Methods: A qualitative study that involved 12 GP. All was consented to participate in an in-depth interview with the experts by online meeting with 15-20 minutes duration. Analysis was focused on the definition, classification, clinical manifestation, diagnosis, and early management of SpA in primary care. Results: All GP were interviewed (12 GP, 9 men, and 3 women; mean age 29.42) with average years in clinical practice was 3.8 years. All GP could describe the definition of SpA. Only a few subjects are aware of the subtype of SpA. Most of the GP could mention chronic back pain as the main SpA symptom, some GP mentioned extra-articular manifestation, but incomplete. All GP understood the current treatment in clinical practice. Conclusion: GP is aware of SpA, but not all could completely mention the type and clinical entities. In addition, a limited resource for investigation makes a diagnosis of SpA difficult. Current early treatment has been acceptable in clinical practice. A comprehensive understanding of diagnosis and effective early treatment may reduce delayed diagnosis and improve patients' quality of life.